Indonesia - Supandi; Hermanto (LPPM UNIKA Santo Thomas Medan, 2022)
Abstract The development of information technology and especially networks is very rapid. Therefore, it is demanded to have a network system that can monitor the network quickly. Where an admin can quickly find out the network problem is on or off. This research was conducted to monitor the internet network at SMKN 1 Gunungguruh by means of display forms and information in the form of telegram notification messages about network conditions being monitored and sending data real-time to the administrator. With the hope that administrators can quickly handle network problems at SMKN 1 Gunungguruh. The results of the study show that network monitoring using the dude application with telegram notifications can be done in real time and an administrator can quickly find out network problems that occur.